Anaerobic Co-digestion of Expired Dairy Products and Synthetic Domestic Wastewater: Effect on Methane Potential in Batch Reactors - Marin, Danieli Fernanda Canaver [UNESP] (2024)
Substantial amounts of expired dairy products (EDP) are generated due to their high perishability. These wastes are rich in organic matter, and their landfill disposal negatively impacts the environment. An alternative to reducing and recovering this waste would be to use it as a substrate in anaerobic digestion (AD) to produce biogas. This study investigated methane (CH4) production using different concentrations of EDP co-digested with synthetic domestic wastewater (SDW). Five anaerobic batch reactors (1000 mL) were assembled with different concentrations of EDP in SDW (500 mL working volume), namely (1) 0%, (2) 5.0%, (3) 7.5%, (4) 10.0%, and (5) 15.0% (v/v). COD removals were 81%, 84%, 80%, 89%, and 14% for assays 1 to 5, respectively. The cumulative CH4 productions were (mL/L) 717, 3354, 5327, 6584, and 1156 for assays 1 to 5, respectively. Assay 5 (15% EDP) was inhibited by volatile fatty acid (VFA) accumulation. However, assays 2, 3, and 4 (with 5.0–10.0% EDP) showed high CH4 yields (mLCH4/gVSadd) of 319, 333, and 317, respectively, demonstrating the feasibility of anaerobic co-digestion of EDP with SDW. In assays 3 and 4, a similar archaeal community structure was observed, dominated by the genera Methanosaeta, Methanolinea, Methanoregula, and Methanobacterium. In assay 2, the archaeal community demonstrated lower dominance due to insufficient substrate adaptation. This study confirms the viability of using EDP in AD systems to generate CH4, suggesting future sustainable applications for this residue. Graphical Abstract: (Figure presented.)